Metodologia para decisão do poder dióptrico de lentes intraoculares utilizando MTF - Rodrigo de Abreu (2020)
This work proposes a methodology and a metric based on the Modulation Transfer Function (MTF) to assist ophthalmologists during intraocular lens (IOLs) power calculation in the cataract surgery, in which the natural lens is replaced by an artificial one. The suggested methodology is based on the simulations of a semi-custom model of the human eye whose parameters are taken by means of a corneal topographer and an optical biometer. Results are analyzed using image quality assessment techniques, without taking into account psychophysical effects and aspects of neurovision. An algorithm was developed to allow the simulations considering data from different eyes, refractive powers and distinct types of IOLs, also allowing the evaluation of the expected visual acuity taking into account different object distances and toric IOL alignment. The theoretical grounds and reasons of this work are presented and discussed by means of the simulation results of the pseudophakic eye model whereby the anterior corneal surface was represented by a mathematical description that includes the geometric imperfections (aberrations) of the anterior cornea. To accomplish this goal, data of 10 eyes were scaned and the data were used to build a semi-custom eye model. Codes are proposed for: obtaining the mathematical model of corneal topography through Zernike polynomials, integration with the Zemax software, acquisition of the results and data processing. Analyzis considering spherical and toric intraocular lenses and different toric IOL alignment are discussed in order to clarify the scope of the proposed method. The results obtained in the simulations with the method proposed in this work are contrasted with simulations using simplified corneal representations and the IOL power calculated using empirical formulas (technique usually employed by ophthalmologists). Considering only eyes with corneal astigmatism below 1.5 D, the refractive optical powers reported by the optical biometer, based on the empirical equations, result in values that varied up to 1.0 D, depending on the formula employed. The results suggest that the proposed methodology can be used to make a more assertive choice in the calculation of refractive power due to the greater degree of customization compared to the traditional formulas, also allowing the evaluation of the expected acuity considering the different refractive powers, distances of the object and the constructive characteristics of the artificial lens. In addition, the proposed method allows the expected visual acuity to be evaluated by considering various types of IOLs (spherical, aspheric, toric, etc.), which may lead to a more appropriate choice not only of the refractive power but also of the type of intraocular lens to be used in the surgery.